Development of the System of Club Education in Ukraine at the End of the XX – Beginning of the XXI Century - Dmytro Ovsiyenko (Pedagogical Discourse, 2014)
The article analyzes the current problems of the system of club education in higher educational establishments of I-II levels of accreditation. The attention is paid to the priorities facing clubs to enhance the prestige of the club work. The negative trends in the work of the cultural establishments of the club type, including sharp reduction of the network of the later during the last decads have been mentioned. Activity of the new type of cultural institutions that emerged after Ukraine had gained its own independence has been studied. The basic requirements for persons working in the field of culture have been studied. The peculiarities of activity of institutions of culture club type in the Soviet and post-Soviet period have been compared. The importance of the processes that contribute to the revival of Ukrainian traditions, ceremonies for the future professional activity of the workers of club establishments has been proved.